Evaluation of Knowledge and Opinions on Apitherapy Products among 1st and 4th Year Nutrition and Dietetics Department Students - Coşkun, Ayfer Beyaz; Turkoglu, Semra (My University, 2024)
Objective: Apitherapy is a traditional treatment method where honey bee products are used for treatment. Students studying in the Department of Nutrition and Dietetics are not very involved in the application of apitherapy. Material-Method: This study investigates the knowledge and opinions of 1st and 4th year students studying in the Department of Nutrition and Dietetics about apitherapy. A survey was applied to students who were randomly selected in the 1st year (n=168) and 4th year (n=241). The survey questioned information about the descriptive characteristics of the students, knowledge, experience and expectations regarding apitherapy, and the use and frequency of apitherapy products. Results: The most preferred bee product among 1st and 4th year students was found to be honey, followed by bee pollen. The source of information about apitherapy was mostly the internet (63.5%) in 1st year students, while it was the media (46.1%) in 4th year students. When asked who should be the source of information about apitherapy, the majority of 1st year students (64.0%) and 4th year students (67.2%) responded as dietitians. The majority of students in both periods did not have sufficient knowledge and opinion about bee products. Conclusion: This study showed that apitherapy knowledge and opinion among future dietitians are limited. Placing apitherapy in the curriculum and creating and disseminating the apitherapist dietitian identity will increase the tendency of dietitians to use apitherapy.
Keywords: Nutrition; Curriculum; Apitherapy; Dietitian